Explaining Voter Loyalty in Indonesia's Regional Representative Election: The Case of Cerint Iralloza Tasya in West Sumatra - Diffa Khoirunnisa (Pencerah, 2026)
The 2024 General Election and the subsequent Re-vote (PSU) in West Sumatra present an intriguing case study in voter behavior dynamics, featuring a young female candidate and recent graduate—Cerint Iralloza Tasya—who secured the highest number of votes in the 2024 West Sumatra Regional Representative Council (DPD) election. This study aims to describe the consistency of voter behavior among Cerint’s supporters during the 2024 DPD RI election in West Sumatra. It employs a qualitative approach utilizing a case study method, grounded in the voter behavior theory proposed by Adman Nursal. Psychological factors played a significant role; the initial election victory created a perception of her as a